2017
DOI: 10.1136/oemed-2016-103963
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic dust exposure on long-term change in lung function: a systematic review and meta-analysis

Abstract: Lung function is a predictor of morbidity and mortality, and the chronic nature of lung function decline allows for preventive initiatives. Proinflammatory constituents of organic dust are considered a possible cause of compromised respiratory health. The aim of this systematic review was to reveal the impact of organic dust exposure on long-term change in lung function. The literature search was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
2
23
0
1
Order By: Relevance
“…A clear decline in lung function after short term exposure to organic dust, specifically endotoxin, has been firmly established in experimental and occupational studies (Castellan et al, 1987;Michel et al, 2002;Möller et al, 2012;Smid et al, 1994). Evidence with respect to long-term exposure and accelerated lung function decline is limited (Bolund et al, 2017). In our study population, we did not observe a clear decrease in lung function in relation to long-term endotoxin exposure.…”
Section: Endotoxin and Healthsupporting
confidence: 41%
“…A clear decline in lung function after short term exposure to organic dust, specifically endotoxin, has been firmly established in experimental and occupational studies (Castellan et al, 1987;Michel et al, 2002;Möller et al, 2012;Smid et al, 1994). Evidence with respect to long-term exposure and accelerated lung function decline is limited (Bolund et al, 2017). In our study population, we did not observe a clear decrease in lung function in relation to long-term endotoxin exposure.…”
Section: Endotoxin and Healthsupporting
confidence: 41%
“…Thirdly, results may depend on study designs and on methods of population sampling. For example, several cross-sectional studies found that farming jobs exposing workers to organic dusts were associated with increased prevalence of COPD,15 16 whereas a recent meta-analysis including only longitudinal studies concluded that there was limited evidence for a causal association between occupational exposure to organic dust and decline of lung function 17. In addition, many studies did not include a control group of subjects unexposed to any agricultural environment, which may also lead to some bias.…”
Section: Introductionmentioning
confidence: 99%
“…Een andere systematisch literatuuronderzoek naar het lange-termijn effect van hogere endotoxineconcentraties op de longfunctie liet slechts beperkt bewijs zien van een dergelijk effect. 36 Dit lijkt consistent met de ruimtelijke analyses voor de VGO populatie, zoals die eerder zijn gepubliceerd en specifiek voor de associaties met endotoxine zijn opgenomen in deze studie. 37 De literatuurstudie geeft wel aanwijzing voor korte-termijneffecten op de longfunctie en voor associaties met luchtwegklachten.…”
Section: Conclusiesunclassified